Analisis Determinan Financial Management Behavior sebagai Modal Sosial Perempuan Gen Milenial dan Gen Z Menuju Indonesia Emas 2045 - Apriani, Erna; Latif, Abdul; Aprilianti, Aprilianti (Universitas Batanghari Jambi, 2025)
The purpose of this study is to analyze the determinants of financial management behavior as a social capital for Millennial and Gen Z women. Data analysis in this study uses associative causality with a quantitative approach. The sample in this study is the gender of the millennial and Gen Z generation women who are already working with a focus on the three largest industrial areas in West Java, namely Bekasi, Karawang, and Purwakarta Regency. The research sampling technique used the Slovin formula with online and direct questionnaires and interviews. The sample determined by the Slovin technique was 400 respondents from 1,008,579 female workers over 15 years old who are working. The results of this study conclude that there is a positive and significant influence between the variables of financial knowledge and personality traits on financial management behavior and on education level. There is a positive and significant influence between the variable of education level on financial management behavior. In addition, this study also found that the variable of education level was not able to moderate the influence of the variable of financial knowledge on financial management behavior. However, the variable of education level was able to moderate the influence of the variable of personality traits on financial management behavior as a social capital for Millennial and Gen Z women.